2016
DOI: 10.7150/jca.15667
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Decarboxylase 1 Overexpression as a Poor Prognostic Factor in Patients with Nasopharyngeal Carcinoma

Abstract: Background: Glutamate decarboxylase 1 (GAD1) which serves as a rate-limiting enzyme involving in the production of γ-aminobutyric acid (GABA), exists in the GABAergic neurons in the central nervous system (CNS). Little is known about the relevance of GAD1 to nasopharyngeal carcinoma (NPC). Through data mining on a data set derived from a published transcriptome database, this study first identified GAD1 as a differentially upregulated gene in NPC. We aimed to evaluate GAD1 expression and its prognostic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…GAD1 is a rate-limiting enzyme in the production of γ-aminobutyric acid (GABA) and found in the GABAergic neurons in the central nervous system. In contrast to previous findings that reported an elevated GAD1 expression in oral, nasopharyngeal, and gastric cancers [59,60], we detected a significant decrease in GAD1 expression in cervical cancer tissues. The impaired GAD1 expression may be related to the gene hypermethylation in some neoplastic tissues [61].…”
Section: Discussioncontrasting
confidence: 99%
“…GAD1 is a rate-limiting enzyme in the production of γ-aminobutyric acid (GABA) and found in the GABAergic neurons in the central nervous system. In contrast to previous findings that reported an elevated GAD1 expression in oral, nasopharyngeal, and gastric cancers [59,60], we detected a significant decrease in GAD1 expression in cervical cancer tissues. The impaired GAD1 expression may be related to the gene hypermethylation in some neoplastic tissues [61].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, high CMIP levels were associated with worse prognosis (recurrence-free and overall survival) in gastric and breast cancers [43,45] and were related with herceptin resistance in HER2-positive gastric cancer cells [46]. Similarly, the enzyme encoded by GAD1 gene, which catalyzes the conversion of L-glutamic acid to γ-aminobutyric acid, has been found overexpressed in several types of tumors, including lung adenocarcinoma [47], nasopharyngeal carcinoma [48], oral squamous cell carcinoma [49], prostate cancer [50], and brain metastasis [51], being also found upregulated in colon and HCC cells in vitro [52]. In parallel, high GAD1 levels were also shown to correlate with the pathological stage of patients with lung adenocarcinoma, positively correlating with metastasis and with worse recurrence-free survival [47].…”
Section: Discussionmentioning
confidence: 99%
“…Over expression of GAD1 has been found in several cancers (including oral cancer, colorectal carcinoma, breast cancer, lymphoma and gastric cancer) and it can influence the proliferation, metastasis and chemoresistance of cancer cells [18][19][20]. Increasing research suggests that GAD1 has the potential to be a biomarker for prognosis prediction [21][22][23][24]. Tsuboi et al found that upregulation of GAD1 in lung adenocarcinoma patients showed significantly poorer prognosis for overall survival [22].…”
Section: Discussionmentioning
confidence: 99%